Sexual health, risky sexual behavior and condom use among adolescents young adults and older adults in chiang mai, thailand: Findings from a population based survey - Kanokporn Pinyopornpanish (2018)
© 2017 The Author(s). Background: Sexual health is one of the key dimensions of health across all ages. Understanding risky sexual behaviors remains an important area of public health research. This study aimed to explore sexual health, risky sexual behaviors and factors associated with recent condom use as condom use is considered a main intervention proven to reduce negative health consequences of risky sexual behaviors, specifically related to sexually transmitted infections and unintended pregnancies. A stratified two-stage cluster sampling technique survey was conducted in Chiang Mai, Thailand. Information was obtained about age of first sexual intercourse, sexual activity, condom use, number of partners and history of drug/alcohol use prior to sexual activities within the past 3 months. A weighted analysis was performed to account for data clustering. Results: It is estimated that most men (93%) and women (86%) in Chiang Mai have engaged in sexual intercourse. More than 70% of the people in Chiang Mai over age 30 remained sexually active in the past 3 months, even for populations over age 50. Eight percent of male teenagers reported having more than one sexual par tner in the past 3 months. Regular condom use was reported in less than 5% of the population (6.6% men and 3.1% women). Conclusions: Our study demonstrated that sexual health is an important public health issue across all age groups. Condom use has been promoted as one way to minimize and prevent unintended consequences of sexual behavior but overall use remains low.